Review on the Thermo-Electric Power Generation - Sharma, Sharad; Singh, Fatehbir (IJRDO - Journal of Electrical And Electronics Engineering, 2015)
The Thermoelectric power generation technology provides attractive alternative generation potential to the electric power utilities. In this paper on Thermoelectric technology an outline of the technology and its future in the energy reserves is covered. This paper also discusses the recent developments taking place in thermoelectric effect power generation in India.